Blastocyst complementation and interspecies chimeras in gene edited pigs - Choe, Yong-ho; Sorensen, Jacob; Garry, Daniel J.; Garry, Mary G. (Frontiers in Cell and Developmental Biology, 2022)
The only curative therapy for many endstage diseases is allograft organ transplantation. Due to the limited supply of donor organs, relatively few patients are recipients of a transplanted organ. Therefore, new strategies are warranted to address this unmet need. Using gene editing technologies, somatic cell nuclear transfer and human induced pluripotent stem cell technologies, interspecies chimeric organs have been pursued with promising results. In this review, we highlight the overall technical strategy, the successful early results and the hurdles that need to be addressed in order for these approaches to produce a successful organ that could be transplanted in patients with endstage diseases.